Choroidal Thickness in Relation to Bone Mineral Density with Swept-Source Optical Coherence Tomography - Lin Jiang; Yiwen Qian; Qingjian Li; Jing Jiang; Yu Zhang; Xin Che; Zhiliang Wang (Journal of Ophthalmology)
Purpose. To assess whether bone mineral density, indicated by the lumbar X-ray scan, is related to changes in choroid thickness in normal subjects. Methods. This study included 355 patients with decreased bone mineral density and 355 age- and sex-matched healthy subjects. Lumbar BMD was measured by dual-energy X-ray absorptiometry (DXA). Choroidal thickness was measured using swept-source optical coherence tomography (SS-OCT). Blood pressure (BP), cholesterol, triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were recorded on the same day. Results. There was a significant difference in average choroidal thickness between low BMD subjects and normal subjects p=0.003. The BP, cholesterol, triglyceride, HDL, and LDL showed no significant difference between the two groups. The correlations showed that average choroidal thicknesses were associated with BMD in the entire population (r = 0.125, p=0.001). Conclusion. The choroidal thickness is thinner in low BMD populations compared with normal individuals. There is a strong positive correlation of choroidal thickness with BMD, regardless of age, sex, and other demographic and clinical factors.